Clinicians' views of using cortical auditory evoked potentials (CAEP) in the permanent childhood hearing impairment patient pathway. (1st February 2020) - Mehta, Kinjal; Mahon, Merle; Van Dun, Bram; Marriage, Josephine; Vickers, Deborah
Abstract: Objective: To obtain clinicians' views on the use of cortical auditory evoked potentials (CAEP) in the clinical pathway. Design: A questionnaire aimed at clinicians who use the HEARLab system with the Aided Cortical Assessment (ACA) Module. Results compared for Australians (where HEARLab produced) to other countries. Sample: The questionnaire was completed by 49 clinicians; 33 from Australia and 13 clinicians outside of Australia and 3 clinicians, destination unknown. Results: The findings of this research demonstrated that clinicians using CAEPs found them valuable for clinical practice. CAEPs were used to verify or modify hearing aid fittings and were used for counselling parents to reinforce the need for hearing aids. With the use of speech token as the stimulus clinicians had more relevant information to increase confidence in decision-making on paediatric hearing management. Conclusions: The main benefit from the use of CAEPs (using speech token stimuli) was for infant hearing aid fitting programmes, to facilitate earlier decisions relating to hearing aid fitting, for fine-tuning the aids and as an additional measure for cochlear implant referrals.